If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 8) + -1x = 8 Reorder the terms: 3(8 + 3x) + -1x = 8 (8 * 3 + 3x * 3) + -1x = 8 (24 + 9x) + -1x = 8 Combine like terms: 9x + -1x = 8x 24 + 8x = 8 Solving 24 + 8x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 8x = 8 + -24 Combine like terms: 24 + -24 = 0 0 + 8x = 8 + -24 8x = 8 + -24 Combine like terms: 8 + -24 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 3(4x+5)+2=3 | | 19-8d=-17 | | 10g=-4/6 | | 2x+7y=126 | | m/8=16 | | 11x^2-47y+12=0 | | 12-17=89 | | -5+1/4m=-7 | | 72=x+15 | | 1/2(6x+4)=2x-11 | | 4y^2-15y+9=0 | | 18-3x(4+(-8))+5x=10x-2 | | 2(x+-9)=-10 | | -5+1/4(-2)=-7 | | 8(3-y)-4=-(2-y)-9y | | 2m+1/3-m-6/4=2m+4/8+2 | | x^2+7xy^2=0 | | 15+3x=21 | | 8*x=17/2 | | 2m+1/3-m-6/4=2m | | 1/2y+x=-10 | | -3x+3=-2x+1 | | 4(3-2x)+2=2 | | (5b)*(-9x)= | | 2*cosx*sinx-cosx=1 | | 7(2+5h)=-17 | | C+9=18 | | 7(2+5h)=-71 | | 6+1.25a=1.1a | | (x^2+12x+40)/(x+7) | | 13/5=n | | .02-.05x+.3x=-.68 |